2019
DOI: 10.20867/tosee.05.45
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation in Tourism Education

Abstract: Purpose -Digital technology is an undeniable prime mover of society, and the ongoing digital transformation seems to be increasing the challenges within Tourism Education. Thus, this study aims at identifying, in the literature, advantages and constraints it poses to the area. Methodology -This work follows a literature review methodology, focusing on peer-reviewed, open source, recently published research, and the selected papers were analysed though a content analysis. Findings -The results yielded that teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…The above responses also revealed that the activities adopted in this study benefitted the students by increasing interaction and collaboration, as promoted by Kinyanjui (2019), and providing a learnercentered approach, as emphasized by Inoue and Bell (2006) and He et al (2019). These results echo the needs raised by Balula et al (2019) and Patiar et al (2017) to integrate ICT with professional developments in tourism and hospitality education.…”
Section: The Students' Responses To the Effectiveness Of The Ict-enhasupporting
confidence: 64%
See 2 more Smart Citations
“…The above responses also revealed that the activities adopted in this study benefitted the students by increasing interaction and collaboration, as promoted by Kinyanjui (2019), and providing a learnercentered approach, as emphasized by Inoue and Bell (2006) and He et al (2019). These results echo the needs raised by Balula et al (2019) and Patiar et al (2017) to integrate ICT with professional developments in tourism and hospitality education.…”
Section: The Students' Responses To the Effectiveness Of The Ict-enhasupporting
confidence: 64%
“…Several studies adopted an ICT learning environment into curricula and found that instructors' pedagogical strategies for building a successful supportive learning environment can improve peer interaction and enhance learning motivation and course-directed learning interest (Chang et al, 2010;Xue, 2020;Zhang et al, 2020) The tourism and hospitality industries have seen a rise in the use of ICT, as these advancements have become an indispensable asset for businesses (Law et al, 2019). Balula et al (2019) emphasized the need for higher educational institutions to embed ICT skills in tourism curricula. The industry's adherence to globalized technological developments has raised the critical need for future professionals to possess digital literacies (Silva et al, 2019, March, 14-15).…”
Section: Information and Communication Technology (Ict)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the strategic plans of the universities included in the study, such as providing pieces of training on technological transformation to in-university academic staff, can be considered a positive strategy for eliminating generation conflicts in the form of digital native and digital immigrants [38]. Actually, as in the study of A. balula et al [39], negative attitudes towards digital technological innovations may be seen in academicians and pieces of awareness training are recommended for such resistances.…”
Section: Discussionmentioning
confidence: 99%
“…As the current tourism education is considered traditional, changes in learning environments, educational methods, and curricula are required (Kalogiannakis, 2010;Hsu, 2018). The crucial role of digital technologies in the tourism sector brings a revolution leading to innovation, changing customers' behaviors, and enhancing their experiences (Balula et al, 2019;Law et al, 2014).…”
Section: Introductionmentioning
confidence: 99%